Health and wealth on the roller-coaster: Ireland, 2003-2011 - David Madden (University College Dublin, UCD School of Economics, 2013)
This paper reviews developments in income and health poverty in Ireland over the 2003-2011 period using data from the Survey of Income and Living Conditions (SILC). It also examines developments in the correlation between the two. Income poverty fell up to and including 2009, after which this trend is reversed. Health poverty shows less of a trend over the period though there is some evidence of a reduction in health inequality from 2006. Movements in bi-dimensional poverty are mostly driven by income poverty, but there is evidence of a reduction in the correlation between health and income poverty over the period.
Keywords: I12; I31; I32; 330; multidimensional poverty; dominance